Evolusi Sistem Pemilihan Umum Indonesia 1955-2009 - M. Zaki Mubarak (Refleksi: Jurnal Kajian Agama dan Filsafat, 2008)
The journey of democracy in Indonesia from 1955 to 2009 has undergone dynamic changes. This article illustrates that the evolution of the electoral system in Indonesia during this period has seen several changes in regulations, participating political parties, the widening gap and fragmentation of ideologies albeit more moderately, improvements in the quality and degree of democracy, and the increasing role of non-parliamentary institutions. One thing that has remained unchanged is that, generally, the electoral system still adheres to the same proportional representation system, albeit transitioning from closed to open proportional systems.